Primary teachers and students’ anxiety toward online instruction during COVID-19 pandemic - Kanokwan Phayponpruek; Prasart Nuangchalerm (Journal of Education and Learning (EduLearn), 2022)
The study explored primary teachers and students’ anxiety toward online instruction during COVID-19 pandemic, the factors affecting anxiety related to online instruction of students and teachers in primary school. This research study was designed to collect data from primary teachers and students on the factors that affect anxiety in online teaching. The informants were 127 students and 11 teachers based on the purpose of the research. Questionnaire concerning general student data, such as gender, grade level, online study equipment, and online learning channels. Factors influencing anxiety in online education in the context of the COVID-19 pandemic, with 23 items for students and 25 items for teachers. Data is collected by online inquiries with students and teachers According to the findings, the general degree of factors influencing anxiety from online instruction in primary school is at moderate level. Physical and mental elements, evaluation and course content are the categories of factors that have the most impact on students’ anxiety toward online learning. Meanwhile, the factors that have the greatest impact on students’ anxiety toward online learning are concerning about their grades and courses are extremely recorded. Students believe that online learning is more challenging than traditional classroom. At the same time, teachers are worried about online assessment, concerns about students who are unable to attend online sessions. Teachers who only use computers to teach online have less anxiety than teachers who use computers, tablets, and mobile phones.